Novel polymer-derived ceramic environmental barrier coating system for carbon steel in oxidizing environments. Issue 5 (May 2017) - Nguyen, Minh Dat; Bang, Jung Won; Bin, An Su; Kim, Soo-Ryoung; Kim, Younghee; Hwang, Kyu Hong; Pham, Vuong-Hung; Kwon, Woo-Teck
Abstract: Polymer-derived ceramic environmental barrier coatings (EBCs) in combination with active fillers are highly attractive due to their facile processing and applicability at elevated temperatures. In this study, several kinds of active and passive fillers were added to polymer-derived ceramics and then coated onto carbon steel, using cheap and simple lacquer methods (such as dip or spray coating). The resultant coating, investigated by Thermal Gravimetric Analysis (TGA), Scanning Electron Microscopy with X-ray microanalysis (SEM/EDS), X-ray Diffraction (XRD), adhesion tests and oxidation tests, showed that it acted as an excellent film to withstand thermal cycling, and prevented carbon steel from being oxidized at elevated temperatures. The low-cost and effective coating method described in this paper can be used widely to protect carbon steel used at high temperatures (e.g. steel boiler tubes in waste-to-energy plants).